Hotel Finca Rosa Blanca Country: Example of corporate social responsibility in Costa Rica - Vasconcelos Vásquez, Kattia Lizzett (2016)
The focus of this article is the relationship between the Certification for Sustainable Tourism (CST) in Costa Rica, which has implemented a management system based on the CST standard, and the Corporate Social Responsibility (RSE). The assessment will find differences and/or similarities between CST and CSR in order to see how they enhance business management and sustainability, and will also highlight the major organizational changes that must be implemented in the institution or company to achieve an